Experimental Study on the Efficacy of Syzygium Aromaticum Against Cutaneous Leishmaniasis in Comparison with Pentostam - Alamri, Zahra Abdullah (Journal of medical and pharmaceutical sciences, 2020)
Cutaneous leishmaniasis is a parasitic disease caused by a kind of ‏ Flagellate (Mastigophora) that belongs to the Leishmania. This disease is transferred by sand flies. This research was conducted to study the effect of Syzygium aromaticum on the evolution of cutaneous leishmaniasis blister in mice infected with this disease. To study the effects of this herb on the evolution of cutaneous blister caused by Leishmania, the white mice of BALB/ c species were injected by a dose of 107 parasitefrom the parasite farm of LON-4 Leishmania major in the sacrum. After three weeks, the blister begins to appear in the injected place like a small tumor (ulceration). It begins to grow into blister then to sore which is often accompanied with bacterial and fungal infection. Experiments were conducted into two parts. The first part includes experiments conducted on mice, while the second part includes the tissue test of cutaneous blister and making sure that it is parasite free. The study covered three groups: the negative control group which is formed from eight mice; positive control group (Pentostam group) and it is formed from eight mice injected by Pentostam drug, 120 mg; Syzygium aromaticum group that was administrated different doses of 5, 10, 40, 60 mgorally before treated directly by ointment of Syzygium aromaticum herb on the blister place. It was found that the infected mice treated by Syzygium aromaticum orally by a dose of 40 mgand also treated by Syzygium aromaticum ointment directly on the blister place gives high percent of improvement reached 72%. Then it is followed by the group treated by Syzygium aromaticum orally by a dose of 60 mgas the percent of improvement reached 52%. The results showed that the Syzygium aromaticum is the best to treat the cutaneous leishmaniasis amongst other herbs.